(U‐Th)/He and 4He/3He Thermochronology of Secondary Oxides in Faults and Fractures: A Regional Perspective From Southeastern Arizona. (24th November 2021) - Scoggin, Shane H.; Reiners, Peter W.; Shuster, David L.; Davis, George H.; Ward, Lauren A.; Worthington, James R.; Nickerson, Phillip A.; Evenson, Nathan S.
Abstract: Fe‐ and Mn‐oxides are common secondary minerals in faults, fractures, and veins and potentially record information about the timing of fluid movement through their host rocks. These phases are difficult to date by most radioisotopic techniques, but relatively high concentrations of U and Th make the (U‐Th)/He system a promising approach. We present new petrographic, geochronologic and thermochronologic analyses of secondary oxides and associated minerals from fault zones and fractures in southeastern Arizona. We use these phases in attempt to constrain the timing of fluid flow and their relationship to magmatic, tectonic, or other regional processes. In the shallowly exhumed Galiuro Mountains, Fe‐oxide (U‐Th)/He dates correspond to host‐rock crystallization and magmatic intrusions from ca. 1.6 to 1.1 Ga. Step‐heating 4 He/ 3 He experiments and polydomain diffusion modeling of 3 He release spectra on these samples are consistent with a crystallite size control on He diffusivity, and little fractional loss of radiogenic He since formation in coarse‐grained hematite, but large losses from fine‐grained Mn‐oxide. In contrast to Proterozoic dates, Fe‐ and Mn‐oxides from the Catalina‐Rincon and Pinaleño metamorphic core complexes are exclusively Cenozoic, with dates clustering at ca. 24, 15, and 9 Ma, which represent distinct cooling or fluid‐flow episodes during punctuated periods of normal faulting. Finally, a subset of Fe‐oxides yield dates of ca. 5 Ma to 6 ka and display either pseudomorphic cubic forms consistent with oxidative retrogression of original pyrite or magnetite, or fine‐grained botryoidal morphologies that we interpret to represent approximate ages of recrystallization or pseudomorphic replacement at shallow depths. Plain Language Summary: (U‐Th)/He dating is increasingly applied to secondary Fe‐ and Mn‐oxide minerals in an attempt to understand the timing of fluid‐rock reactions associated with magmatic intrusions, fault activity, or other forcings. However, accurate interpretations of secondary oxide thermochronology data requires consideration of potential complications that can lead to multiple interpretations. Here we present (U‐Th)/He and 4 He/ 3 He thermochronologic analyses along with chemical and textural observations and provide a geologic context for secondary Fe‐ and Mn‐oxides from southeastern Arizona, in an attempt to better understand how the data relate to geologic processes. Many of these minerals formed and/or cooled in fault zones and fractures at times associated with magmatic or tectonic activity, but some were also recrystallized or pseudomorphically replaced by later fluid‐rock reactions. We also provide evidence that He diffusivity is governed by crystal sizes, and that crystal shape and chemical composition should be considered when interpreting (U‐Th)/He data of Fe‐ and Mn‐oxides. Key Points: Step heating experiments and He diffusion modeling of Fe‐ and Mn‐oxides are consistent with a grain size control on He diffusivity Fe‐ and Mn‐oxide (U‐Th)/He dates from southeastern Arizona are consistent with Proterozoic‐Cenozoic magmatic and tectonic events Petrographic and spectroscopic characterizations of Fe‐ and Mn‐oxides help provide context for (U‐Th)/He data interpretation